HCV infection and the risk of head and neck cancer: A meta-analysis. (October 2020) - Borsetto, Daniele; Fussey, Jonathan; Fabris, Luca; Bandolin, Luigia; Gaudioso, Piergiorgio; Phillips, Veronica; Polesel, Jerry; Boscolo-Rizzo, Paolo
Highlights: HCV-positive people have about 2-fold higher risk of head and neck cancers. Co-infection with HIV does not substantially modify this association. Surveillance in HCV+ patients favors early diagnosis of head and neck cancer. Occult HCV in head and neck cancer patients should be considered by oncologist. Abstract: Recent evidence has consistently suggested a role for HCV in the etiology of head and neck squamous cell carcinoma (HNSCC), but the conclusions of these studies have often been limited by small sample size. Therefore, a meta-analysis was performed to summarize present evidence on the association between HCV infection and HNSCC. After screening citations from literature search, eight observational studies investigating the association between HCV and cancer(s) of either oral cavity, oropharynx, hypopharynx or larynx were included. For each cancer site, risk ratios from individual studies were displayed in forest plots; pooled risk ratios (RR) and corresponding confidence intervals (CI) were calculated. A significant association was found between HCV infection and cancers of the oral cavity (RR = 2.13; 95%: 1.61–2.83), oropharynx (RR = 1.81; 95% CI: 1.21–2.72), and larynx (RR = 2.57; 95% CI: 1.11–5.94). A similar picture emerged for hypopharyngeal cancer, though this result did not fully reach statistical significance because of the small number of available studies (RR = 2.15; 95% CI: 0.73–6.31). These findings remained similar after exclusion of patients with HIV co-infection. Our results highlighted the importance of surveillance of the upper aerodigestive tract in patients with known chronic HCV infections in order to enable HNSCC early diagnosis. In addition, they could be a reminder of the possibility of undiagnosed HCV infection to the clinicians treating HNSCC.